PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) BERBANTUAN VIDEO ANIMASI TERHADAP HASIL BELAJAR BAHASA INDONESIA KELAS V SD NEGERI 060885 MEDAN BARU - Maria Nainggolan, Venia; Juliana; Julinda Simarmata, Ester; Reflina Sinaga; Dyan Wulan Sari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low learning outcomes of Indonesian language exposition text material for fifth-grade students of SD Negeri 060885 Medan Baru, where only 40% of students achieved the completion criteria. This study aims to examine the effect of the Contextual Teaching and Learning (CTL) learning model assisted by animated videos on the learning outcomes of fifth-grade students at the school in the 2025/2026 Academic Year. The approach used is quantitative with a One Group Pretest-Posttest Design on a population and a total sample of 30 students. Data were collected through learning outcome tests, student response questionnaires, and documentation, then analyzed using normality tests, product-moment correlation tests, and t-tests. The results showed a significant increase in the class average score from 52.6 in the pretest to 80.4 in the posttest, with the completion rate jumping from 6.7% to 86.7%. Based on the hypothesis testing, the t-count value was 3.774, which was greater than the t-table value of 2.048, and the significance value was 0.001 < 0.05. The correlation coefficient value of 0.581 also indicated a fairly strong relationship. Therefore, it can be concluded that the implementation of the CTL learning model assisted by animated videos has a positive and significant effect on students' Indonesian language learning outcomes.